A Qualitative Study on Young Women’s Lives Prior to and Four Years after Youth Detention: Examining the Good Lives Model’s Aetiological Assumptions - Lore Van Damme (MDPI AG, 2021)
Detained female adolescents constitute a vulnerable, challenging, and understudied minority. Interventions for DFA are still dominated by risk management approaches with less focus on strength-based approaches such as the Good Lives Model (GLM). This study explored the functionality of DFA’s behaviour prior to and four years after release from detention, using the GLM as the guiding theoretical framework. A theory-driven thematic analysis was conducted of 30 in-depth interviews with former DFA (Mage = 20.80), exploring the fulfilment of their basic human needs (e.g., relatedness, independence) before and after detention. Before detention, the young women experienced multiple problems trying to fulfil multiple human needs, often contributing to poor balance in their lives and their antisocial behaviour. Although external and internal obstacles to fulfilling human needs were still present at follow-up, important improvements were noted, e.g., in the scope of their human needs and the resources available to fulfil their needs. The findings provide additional insights into the issues experienced by young women in detention and indicate there are opportunities to assist these young women, through the development of appropriate resources and capacities which provide them with appropriate means for fulfilling their needs and moving towards a personally meaningful and prosocial life.